2018
DOI: 10.1039/c7cp08154e
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the thermoelectric performance of gamma-graphyne nanoribbons by introducing edge disorder

Abstract: Structure disorder especially edge disorder is unavoidable during the fabrication of nanomaterials. In this paper, using the non-equilibrium Green's function method, we investigate the influence of edge disorder on the thermoelectric performance of gamma(γ)-graphyne nanoribbons (GYNRs). Our results show that the high Seebeck coefficient in pristine γ-GYNR could still be preserved although edge disorder is introduced into the structure. Meanwhile, in these edge-disordered nanoribbons the suppression of thermal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 54 publications
0
8
0
Order By: Relevance
“…This wide band gap indicates that double vacancy in γ-graphyne will lead to a large Seebeck coefficient. Literature survey also reveals that the introduction of the defective environment in the γ-graphyne nanoribbon system significantly enhances the thermoelectric performance of the material. Therefore, we expect further enhancement with defects in our structures too.…”
Section: Resultsmentioning
confidence: 84%
“…This wide band gap indicates that double vacancy in γ-graphyne will lead to a large Seebeck coefficient. Literature survey also reveals that the introduction of the defective environment in the γ-graphyne nanoribbon system significantly enhances the thermoelectric performance of the material. Therefore, we expect further enhancement with defects in our structures too.…”
Section: Resultsmentioning
confidence: 84%
“…On the other hand, (Tran et al, 2015) found the phonon conductance is significantly inhibited in GNRs with BNNRs branches, but the electron transmission is equivalent to that in pristine GNRs, similar to that in vdW graphene junction (Hung Nguyen et al, 2014). Moreover, (Cui et al, 2018b) reported that the ZT value of graphyne nanoribbons with edge disorder can achieve 2.5 because of the strong phonon-boundary scatterings. Along the way, the MoS2/WSe 2 (Jia et al, 2019) and graphene/ MoS 2 vdW heterostructures (Sadeghi et al, 2016) have been proposed to construct thermoelectronic devices with excellent performance.…”
Section: Thermoelectric Conversionmentioning
confidence: 89%
“…Edge disorder can greatly improve the thermoelectric conversion rate of g-GYNRs. 121,122 Different defect structures and different defect locations also have a critical effect on the power factor and thermal conductivity suppression of GYNRs and GDYNRs. Researchers can significantly enhance the thermoelectric properties of g-GYNRs, through edge defect modulation (by a factor greater than 1.2 at room temperature) (Fig.…”
Section: Thermodynamic Properties and Thermoelectric Propertiesmentioning
confidence: 99%
“…(e) The maximum value of the edge disordered g-GYNR thermoelectric superiority is a function of the length of the central region (M = 0.3, the central region width is fixed at 1.41 nm) and the width (M = 0.3, the central region length is fixed at 13.92 nm), where the shaded part is an error bar. The dashed lines represent the corresponding values of the original g-GYNR 122. (f) Thermal power (ZT) and phonon thermal conductance (P) after the original and edge defect modulation g-GYNR (W = 3) 111.…”
mentioning
confidence: 99%